Food, energy, and water the chemistry connection - Ahuja, Satinder 1933- (Elsevier, 2015)
Food, Energy, and Water: The Chemistry Connection examines the inextricable link among the vital resources of food, energy, and water to explain how this relationship should be considered in contemporary research and development. This book will help scientists balance competing concerns of environmental stewardship and innovative, cost-effective product development. Detailed discussions cover how we can utilize these resources without depleting them or decreasing their quality.--Provided by publisher.